Toxic Productivity Among University Students: The Role of Institutional Policy and Student Experience Perspectives - Laila Sabrina; Ratna Dewi; Arizal Mutahir; Wiman Rizkidarajat (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Toxic productivity has become increasingly prevalent among university students as academic expectations, social pressures, and institutional policies collectively shape a culture that normalizes continuous activity. This study examines the phenomenon within the Faculty of Social and Political Sciences at Universitas Jenderal Soedirman by exploring how students interpret productivity-oriented academic regulations and how these structures interact with psychological tendencies. Using a descriptive quantitative design, data were collected from 233 undergraduate students through a structured questionnaire employing Likert and Guttman scales and analyzed using frequency distributions and descriptive statistics to identify behavioral patterns, perceptions of institutional policies, and experienced impacts. The findings show that many students experience persistent pressure to remain productive, often accompanied by guilt during rest, academic overload, and declining well-being. Students perceive institutional requirements, such as mandatory organizational involvement and credit-based activity systems, as reinforcing an achievement-oriented environment that promotes excessive productivity. These results demonstrate that toxic productivity arises not only from personal or social factors but also from structural academic expectations that shape bounded rationality in student decision-making. The study concludes that policy adjustments that promote flexibility, balanced performance indicators, and improved mental health support are essential to mitigating excessive productivity pressures and fostering healthier academic conditions. Keywords: burnout, mental health interventions, toxic productivity, university policy, well-being